Geography teachers’ implementation of problem-based learning for deforestation and climate change education in Metekel Zone Secondary Schools, Northwest, Ethiopia - Wahelo, Tamiru Toga; Mengistu, Daniel Ayalew; Merawi, Tadesse Melesse (International journal of educational development, 2025)
Environmental problems related to deforestation and climate change pose serious socio-economic and ecological threats. In Ethiopia, rapid forest loss and climate impacts demand sustainable solutions through education. Problem-based learning (PBL), which fosters critical thinking, collaboration, and real-world problem-solving, is well-suited to address both environmental and pedagogical challenges. This study examines geography teachers’ implementation of PBL for deforestation and climate change education in secondary schools in Metekel Zone, Northwest Ethiopia. A convergent mixed-methods design and multi-stage sampling were used to collect data from 134 geography teachers, 7 department heads, 7 principals, and 3 education experts through surveys, interviews, focus group discussions, and classroom observations. Quantitative data were analyzed using descriptive statistics, one-sample t-tests, Pearson correlation, and binary logistic regression; qualitative data were thematically analyzed. Policy-relevant findings reveal low teacher belief in PBL, limited heuristic strategies, and weak contextualization of environmental content. A strong correlation between belief and practice shows that stronger teacher beliefs foster greater PBL use. Regression analysis identified structural and systemic factors shaping PBL adoption. Positive factors include teacher adaptation, emotional intelligence, student environmental identity, motivation, and content knowledge. Barriers include large class sizes, traditional methods, and the time-intensive nature of PBL. Thematic analysis also highlighted curriculum rigidity, student resistance, and limited resources. The study recommends policy actions including targeted teacher training, flexible curricula, and systemic support to promote PBL in environmental education. Addressing class size, infrastructure, and student engagement is essential for sustaining PBL practices. These findings offer actionable insights for policymakers and educational planners aiming to integrate PBL in response to environmental challenges. •Explores geography teachers' use of PBL in teaching deforestation and climate change topics.•Employs a mixed-methods design involving 134 geography teachers and key stakeholders.•Finds a strong link between PBL beliefs and classroom implementation.•Identifies key enablers and barriers to PBL, including teacher traits, student identity, resources, and class size.•Recommends teacher training, flexible curricula, and better infrastructure to enhance PBL implementation.